Studi Literatur Metode Diagnosis Anisakis - Oriza Surya Ningsih; Annytha I.R Detha; Diana A Wuri (Jurnal Veteriner Nusantara, 2023)
Anisakiasis is a disease caused by Anisakis sp. and classified as a dangerous zoonosis. The main source of infection in humans is consuming raw fish containing Anisakis sp. Larvae. Various diagnostic techniques are being developed to detect the incidence of anisakiasis. Diagnostic techniques currently used are the Rapid test and the molecular test. Molecular techniques have recently been developed as effective tools not only for the diagnosis of individual cases but also for the taxonomic and evolutionary study of anisakis nematodes. This literature study aims to determine the methods and work procedures as well as the level of accuracy of the various methods used to detect Anisakis sp .. Reference sources are taken in the form of articles, theses, journals, and e-books related to the title of the literature study being explored. via Google Scholar and with the help of the Mendeley app. Based on a review of literature studies, it can be seen that the method used to detect Anisakis sp. with a low level of accuracy namely KIT, LAMP Assay and SEM, while the methods with a high level of accuracy are PCR-RFLP and RT-PCR and the most effective methods are used to detect Anisakis sp. are PCR-RFLP and RT-PCR because the processing time is fast and can provide accurate results.